The status of biodiversity in Echuya central Forest reserve, S.W Uganda - Bitariho, Robert; Babaasa, Dennis; Mugerwa, Badru (My University, 2015)
Uganda is losing biodiversity at an alarming rate. Habitat change and direct exploitation by humans are among the most important reasons for this crisis. Forest wildlife is particularly affected with a need for harmonious living through collaborative forest management. This report focuses on the current status of biodiversity in Echuya Central Forest Reserve, SW Uganda. The taxa assessed were the large and small mammals, birds, and plants (trees, shrubs and herbs). Large mammals were surveyed using the camera trapping method, while for small mammals we used Sherman traps, birds were recorded using point counts and mist-nets, and plants were assessed using plots along randomly selected transects. The survey was done in June 2015 for 15 days while the large mammal survey took 30 days. Information on human activities was collected by both camera trapping and transects method. Except for birds, the other taxa are at a very low diversity in Echuya CFR. Ten species of mammals, including humans, were recorded. Human activities were recorded as the most prevalent at 17 of all 27 sites (contributing to 63% of all the surveyed areas). Dogs, cows and goats were also recorded as signs of human presence. The African Giant Pouched Rat (Cricetomys gambianus) was the most recorded non-human mammal species. Three medium sized carnivore species also recorded were the African Golden Cat (Caracal aurata), Serval Cat (Leptailurus serval) and the Side-striped Jackal (Canis adustus). Ten species of small mammals were recorded. Many of these species were forest-dependent species. Three Albertine Rift endemics were recorded: rodents - Lophuromys woosnami and Delanymys brookski and shrew Ruwenzorisorex suncoides. Delanymys brookski is a rare Albertine Rift endemic restricted to montane swamps in the Kigezi area of Uganda and the bordering areas of DR Congo and Rwanda. The most abundant small mammal species were Lophuromys flavopunctatus and Mastomys natalensis. A total of 94 species of birds were recorded for the whole forest of which 15 were Albertine Rift endemics. Because of the forest harboring a substantial number Albertine Rift endemics and globally threatened bird species, it has made the forest a biodiversity hotspot in terms of species rarity both nationally and within the Albertine Rift. A total of 20 species of trees ≥10cm dbh were encountered in the whole forest. All the tree species encountered were early pioneers or ‘secondary’ species and late ‘secondary’ species implying that Echuya is a secondary forest. Macaranga capensis was the most dominant tree occurring in 65% of the sites surveyed. Seventy two species of herbs and 46 of shrubs were encountered in the whole forest. None of the taxa was completely inventoried, as their species accumulation/rarefaction curves never reached asymptote values. This indicated that more species of each taxa are likely to be encountered with more sampling effort. Human activity signs were encountered on 60 out of the 122 sites sampled. Human activity is nearly evenly distributed in the whole forest. Most the activities encountered were; cultivation (gardens) inside a natural forest, cutting of bamboo stems, trees, grazing of livestock and footpaths crossing all through the reserve. There was no relationship between the species assemblages and the measured environmental variables. The environmental variables include slope angle and aspect, slope position, vegetation type, forest cover/canopy openness, altitude, distance from forest boundary, and human activity occurrence. This indicates that species assemblages of each taxa were not habitat specific. Recommendations made after this study include; the zoning of Echuya CFR into different management zones with strict enforcement of the Strict Nature Reserves, the involvement of the local communities in the enforcement of the nature reserves e.g. using the local councils and the need for more intense biodiversity surveys of same sites that are likely to reveal more species since this study was limited in time and labor for such surveys.
Keywords: Biodiversity; Echuya; Central Forest Reserve; Uganda